1997
DOI: 10.1046/j.1365-2567.1997.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial production of MCP‐1: modulation by heparin and consequences for mononuclear cell activation

Abstract: SUMMARYHeparin is a polyanionic glycosaminoglycan (GAG) that can bind with high affinity to a range of cytokines including interferon-c (IFN-c) and members of the chemokine superfamily. This GAG also possesses immunomodulatory activity in vivo and can antagonize the capacity of IFN-c to induce class II MHC antigen expression, and to up-regulate intercellular adhesion molecule-1, by cultured endothelial cells. Previous studies have shown that binding to cell-surface heparan sulphate is essential for optimal act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…24. The cells recovered from the interface were washed twice with DMEM prior to being resuspended at a concentration of 2 Â 10 6 cells/ml.…”
Section: Preparation Of Peripheral Blood Mononuclear Cells (Pbmc)mentioning
confidence: 99%
See 3 more Smart Citations
“…24. The cells recovered from the interface were washed twice with DMEM prior to being resuspended at a concentration of 2 Â 10 6 cells/ml.…”
Section: Preparation Of Peripheral Blood Mononuclear Cells (Pbmc)mentioning
confidence: 99%
“…Endothelial monolayers that had not been exposed to exogenous chemokine showed no significant expression of cell surface MCP-1 (data not shown); this is consistent with a previous study that demonstrated little MCP-1 production by resting EA.hy926 cells. 24 The antibodies used for the detection of heparan sulfate are specific for epitopes known to be important in MCP-1 binding: 10E4 is specific for molecules containing N-sulfated glucosamine, 43 while HepSS-1 binds to O-sulfated, N-acetylated glucosamine residues linked to glucuronic acid. 44 Reconstructed two-color X-Z sections allowed direct visualization of the distribution of both heparan sulfate and MCP-1 within endothelial monolayers after treatment for 60 min with basally applied chemokine (Figure 3b, c).…”
Section: Distribution Of Mcp-1 On Eahy926 Cells By Immunofluorescencmentioning
confidence: 99%
See 2 more Smart Citations
“…Monocyte chemoattractant protein (MCP)-1 production in experimental allergic neuritis MCP-1, a well characterized b-chemokine, is produced by many cell lineages including monocytes, macrophages, lymphocytes, ®broblasts, endothelia, epithelia (Struyf et al, 1998;Douglas et al, 1997), and astrocytes (Adamus et al, 1997;Glabinski et al, 1997;Sun et al, 1997). Its target cells are monocytes, T lymphocytes and NK cells, but not neutrophils (Gu et al, 1997;Schall, 1994;Vaddi et al, 1997) and while a role for MCP-1 in EAE has been proposed (Karpus, 1995) its potential role in experimental allergic neuritis (EAN) has yet to be fully explored.…”
Section: Introductionmentioning
confidence: 99%